The Oxford handbook of Islamic law - Emon, Anver M.; Ahmed, Rumee (Oxford : Oxford University Press, 2015)
The Oxford Handbook of Islamic Law offers a historiographic window into the scholarly treatment of a wide range of topics in the field of Islamic legal studies. Each essay, authored by an expert in the field, situates its subject in relation to historical academic scholarship. The historiographic feature of the volume is deliberate, to appreciate the contested nature of key concepts and topics in Islamic law without taking any particular account for granted. The essays both describe and reflect on scholarly debates, and gesture to future areas of fruitful research.
Islamic Legal Studies: A Critical Historiography / Ayesha S. Chaudhry Ph.D. -- The Mazalim in Historiography / Mathieu Tillier -- Origins of and Influences on Islamic law / Benjamin Jokisch -- The Classical Period: Scripture, Origins, and Early Development / Mariam Sheibani, Amir Toft, Ahmed El Shamsy -- The Age of Development and Continuity, 12th-15th Centuries CE / Marion Katz -- Law in the Ottoman Empire / Haim Gerber -- A Historiography of Islamic Family Law / Lynn Welchman -- Islamic Law and Finance / Anver M. Emon -- Islamic Law and Human Rights / Shannon Dunn -- Islamic Law and Constitutions / Nathan J. Brown, Mara Revkin -- The Historiography of Sunni Usul al-Fiqh / Youcef Soufi -- r Rula Jurdi Abisaab -- A Historiography of Islamic Law in the Mughal Empire / M. Reza Pirbhai -- The Historiography of Islamic Law During the Mamluk Sultanate / Matthew B. Ingalls -- Anglo-Muhammadan Law / Syed Adnan Hussain -- Islamic Law and Gender / Saadia Yacoob -- al-Qaḍi / Mohammad Fadel -- Hisba and Muhtasib
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on December 7, 2018).
Keywords: Islamic law